Antiviral mode of action of bovine dialyzable leukocyte extract against human immunodeficiency virus type 1 infection - Lara Villegas, Humberto Herman; Ixtepan Turrent, Liliana del Carmen; Garza Treviño, Elsa Nancy; Badillo Almaraz, José Isaías; Rodríguez Padilla, María Cristina (2011)
Background: Bovine dialyzable leukocyte extract (bDLE) is derived from immune leukocytes obtained from bovine spleen. DLE has demonstrated to reduce transcription of Human Immunodeficiency Virus Type 1 (HIV-1) and inactivate the nuclear factor kappa-light-chain-enhancer of activated B cells (NF- B) signaling pathway. Therefore, we decided to clarify the mode of antiviral action of bDLE on the inhibition of HIV-1 infection through a panel of antiviral assays. Results: The cytotoxicity, HIV-1 inhibition activity, residual infectivity of bDLE in HIV-1, time of addition experiments, fusion inhibition of bDLE for fusogenic cells and the duration of cell protection even after the removal of bDLE were all assessed in order to discover more about the mode of the antiviral action. HIV-1 infectivity was inhibited by bDLE at doses that were not cytotoxic for HeLa-CD4-LTR-b-gal cells. Pretreatment of HIV-1 with bDLE did not decrease the infectivity of these viral particles. Cell-based fusion assays helped to determine if bDLE could inhibit fusion of Env cells against CD4 cells by membrane fusion and this cell-based fusion was inhibited only when CD4 cells were treated with bDLE. Infection was inhibited in 80% compared with the positive (without EDL) at all viral life cycle stages in the time of addition experiments when bDLE was added at different time points. Finally, a cell-protection assay against HIV-1 infection by bDLE was performed after treating host cells with bDLE for 30 minutes and then removing them from treatment. From 0 to 7 hours after the bDLE was completely removed from the extracellular compartment, HIV-1 was then added to the host cells. The bDLE was found to protect the cells from HIV-1 infection, an effect that was retained for several hours. Conclusions: bDLE acted as an antiviral compound and prevented host cell infection by HIV-1 at all viral life cycle stages. These cell protection effects lingered for hours after the bDLE was removed. Interestingly, bDLE inhibited fusion of fusogenic cells by acting only on CD4 cells. bDLE had no virucidal effect, but could retain its antiviral effect on target cells after it was removed from the extracellular compartment, protecting the cells from infection for hours. bDLE, which has no reported side effects or toxicity in clinical trials, should therefore be further studied to determine its potential use as a therapeutic agent in HIV-1 infection therapy, in combination with known antiretrovirals.